(untitled) (International Journal of Engineering and Computer Science, 2014)
The process of Single channel speech separation is done to efficiently separate the required speech signals from a mixture. In this research paper we used WPST (Wavelet Packet Based Sub-band Transform) to offer a multi resolution property of wavelet transform to increase the efficiency by reducing the number of coefficients required in each sub-band vector to replace the previously used SPWT (Sub-band perceptually weighted transformation).The new approach improves the separation quality and it results lowest error bound in terms of objective measurements such as Perceptual Evaluation of Speech Quality (PESQ)),segmented SNR in comparison with SPWT based features.